IDENTIFICATION OF CHARACTERISTIC MISTAKES MADE BY YOUNG ATHLETES WHO SPECIALIZE IN HAND-TO-HAND COMBAT IN THE DEVELOPMENT OF PUNCHES - Вако, І. І. (Rehabilitation and Recreation, 2021)
The objective of the study is to identify the characteristic mistakes made by young athletes who specialize in hand-to-hand combat, in the development of punches. Methods. To achieve this goal, we used the analysis of documentary materials, qualimetry – the method of expert evaluations. Expert assessment was conducted with the participation of 20 experts (trainers with more than 5 years of experience). Expert assessment is a very specific type of activity that puts forward certain requirements to the expert, in particular the presence of qualimetric competence, which provides clear understanding of the criteria and methods of assessment of the object of study, the construction of rating scales. At the same time, the results of the examination depend on a number of factors: a degree of workload of an expert in the main work, with which, as a rule, the examination is combined; opportunities for personal use of the obtained results; the nature of the conclusions that can be drawn from the results of the assessment of the quality of the object; individual characteristics of an expert. As for the objectivity of the expert, it can be considered as the ability to take into account only the information that is necessary to assess a particular object. It is important to pay attention to the probable bias of the expert, which is to overestimate or underestimate the quality of the object. The structure of the process of athletes' training is based on objectively existing patterns of formation of sportsmanship, which have specific features in specific sports. These patterns are due to factors that determine the effectiveness of competitive activities and the optimal structure of training, the peculiarities of adaptation to the specific means of sports and methods of influence, individual characteristics of athletes, the timing of major competitions and their optimum to achieve the highest results. Our research has expanded the understanding of the characteristic mistakes made by young athletes who specialize in hand-to-hand combat, in the development of punches.